Challenge Problems for Artificial Intelligence - Selman, Bart; Brooks, Rodney A.; Dean, Thomas; Horvitz, Eric; Mitchell, Tom M.; Nilsson, Nils J. (Proceedings of AAAI-96, Thirteenth National Conference on Artificial Intelligence, Portland, Oregon, August 1996. AAAI Press, Menlo Park, California, 1996)
AI textbooks and papers often discuss the big ques- tions, such as how to reason with uncertainty", how to reason e ciently", or how to improve performance through learning." It is more di cult, however, to nd descriptions of concrete problems or challenges that are still ambitious and interesting, yet not so open-ended. The goal of this panel is to formulate a set of such challenge problems for the eld. Each panelist was asked to formulate one or more challenges. The em- phasis is on problems for which there is a good chance that they will be resolved within the next ve to ten years.